2021
DOI: 10.1029/2020gl091511
|View full text |Cite
|
Sign up to set email alerts
|

Global Daytime Variability of Clouds From DSCOVR/EPIC Observations

Abstract: Knowledge of the daytime variability of cloud fraction is pivotal for the accurate determination of the atmosphere's energy balance. Yet, polar orbiting satellites are unable to fully capture daytime variability and individual geostationary satellites only provide measurements for portions of the Earth. In addition, diurnal cloud fraction variations analyzed with General Circulation Models provide results that cannot be reconciled with observations in many situations. Here, we show that the Earth Polychromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
(91 reference statements)
2
7
0
Order By: Relevance
“…We then average the cloud height of all the local time maps across the number of observations for each grid cell and across all years for a particular season, obtaining thus seasonally-averaged maps of cloud height at all local times. This methodology has proven useful in determining diurnal cycles with EPIC data and quantifying the diurnal variability of cloud fraction for low and high clouds consistently with previous research (Delgado-Bonal et al, 2021). Due to EPIC's location at the L1 point, the best pixel resolution is achieved at nadir ( ~8 km); off nadir the pixels become elliptical with the long axis larger by a factor of about 1/ cos(SZA) and the short axis unaffected.…”
Section: Methodssupporting
confidence: 63%
See 3 more Smart Citations
“…We then average the cloud height of all the local time maps across the number of observations for each grid cell and across all years for a particular season, obtaining thus seasonally-averaged maps of cloud height at all local times. This methodology has proven useful in determining diurnal cycles with EPIC data and quantifying the diurnal variability of cloud fraction for low and high clouds consistently with previous research (Delgado-Bonal et al, 2021). Due to EPIC's location at the L1 point, the best pixel resolution is achieved at nadir ( ~8 km); off nadir the pixels become elliptical with the long axis larger by a factor of about 1/ cos(SZA) and the short axis unaffected.…”
Section: Methodssupporting
confidence: 63%
“…In this case, a positive correlation between high cloud fraction and cloud height is observed for most of the globe. High cloud fraction evolves diurnally regardless of the surface type, with higher cloud fraction values in the afternoon than in the morning and noon (see discussion and appendixes in Delgado-Bonal et al, 2021). The diurnal cloud height cycles obtained in this paper (see Figures 2, 3) follow a similar behavior during the day, with cloud height increasing from morning to evening, hence resulting in mostly positive regional correlations.…”
Section: Cloud Fraction/cloud Height Correlationsupporting
confidence: 66%
See 2 more Smart Citations
“…A recent study showed that the SW diurnal variation from the CERES EBAF is somewhat different from the one inferred from the DSCOVR/EPIC observation (Lim et al., 2021). In addition, the rate of daytime cloud fraction changes from DSCOVR/EPIC observations is not symmetric about noon either (Delgado‐Bonal et al., 2021). The diurnal variation of albedo estimated from the Earth Radiation Budget Experiment (ERBE) also shows that the albedo variations are not always symmetric with respect to noon due to variations of cloudiness throughout the day, which are asymmetric about noon (Rutan et al., 2014).…”
Section: Discussionmentioning
confidence: 99%